Educational environment amid COVID-19 pandemic: new security challenges - Victoria A. Baranova; Ekaterina M. Dubovskaya; Olga O. Savina (Национальный психологический журнал, 2020)
Background. of the article is determined by the need to study educational processes and the educational environment in the situation of the COVID-19 pandemic in particular. The objective of the study is to analyze the characteristics of the educational environment determined by the conditions of the COVID-19 pandemic and the requirements of self-isolation and distance learning, as well as psychological threats to the safety of the educational environment in these new conditions. Design A study of to the security of the educational environment in a pandemic was conducted. These threats were identified in an exploratory study in the first month of the self-isolation regime (April 2020). We analyzed information provided by junior psychology university students (n = 31); teachers (n = 19) and psychologists of Moscow schools (n = 6); schoolchildren – pupils of 5–7 grades (n = 76) and parents of schoolchildren (n = 18). All information was collected remotely, provided on condition of anonymity and voluntariness. Discourse processing was carried out by the method of content analysis and thematic analysis with subsequent expert assessment. The chosen methodological plan of qualitative research allowed the use of individual experiences as indicators of mass consciousness for the analysis of collective states. Results. It was revealed that the current situation created by the COVID-19 pandemic significantly changes the concept of «educational environment». The traditional characteristics of the school educational environment are complemented by factors resulting from the process of “expansion” and “shift” of the educational environment, on the one hand from the school environment to the home environment, and on the other hand from the offline format to the online format. The following new perspectives of the educational environment security defined by the situation of self-isolation are highlighted: distance learning; stay in a home environment, diminishing of direct communication; intensification of communication in the network; forced interaction with the immediate environment; the need to coordinate interaction between teachers and parents; the importance of Internet communication; dynamic processes in the family as in a small group, etc. Situations linked to the dynamics of family and interpersonal relationships, health, the physical environment at home, and the online format of the educational process cause the most important emotions in all participants of the educational process during self-isolation. Conclusions. The program of activities of the educational support service in the school environment should be supplemented with experience and new practices of life in isolation. In a situation of «expanded» educational space and distance learning, educational policy is obliged, while leaving school a priority, to take into account the emergence of new priority subjects in the educational environment that require attention.